Respuesta :
Answer:
(-5, 4)
Step-by-step explanation:
Step 1: Substitute−2x−6for y in y=x+9:
y=x+9
−2x−6=x+9
−2x−6+−x=x+9+−x( Add -x to both sides)
−3x−6=9
−3x−6+6=9+6 (Add 6 to both sides)
−3x=15
−3x
−3
=
15
−3
(Divide both sides by -3)
x=−5
Step 2: Substitute−5 for x in y=−2x−6:
y=−2x−6
y=(−2)(−5)−6
y=4 (Simplify both sides of the equation)
Answer in Equation Form:
x=−5
y=4
Answer in Point Form:
(-5, 4)
Answer:
y=12
Step-by-step explanation:
elimination method
y=-2x -6
y=x•2 +9•2
rewrite problems
y=-2x -6
y=2x + 18
the positive and negative 2x cancels out so you are left with y=12